2014
DOI: 10.5194/hess-18-5077-2014
|View full text |Cite
|
Sign up to set email alerts
|

Satellite-driven downscaling of global reanalysis precipitation products for hydrological applications

Abstract: Abstract. Deriving flood hazard maps for ungauged basins typically requires simulating a long record of annual maximum discharges. To improve this approach, precipitation from global reanalysis systems must be downscaled to a spatial and temporal resolution applicable for flood modeling. This study evaluates such downscaling and error correction approaches for improving hydrologic applications using a combination of NASA's Global Land Data Assimilation System (GLDAS) precipitation data set and a higher resolut… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 73 publications
1
18
0
Order By: Relevance
“…The kinematic wave method is used for lateral transport of surface and subsurface runoff, while the diffusion wave (Muskingum-Cunge) method is used for river routing. The model has been applied in many regions, such as the Amazon (Beighley et al, 2009), Congo (Beighley et al, 2011), Susquehanna (Ray et al, 2016;Seyyedi et al, 2014Seyyedi et al, , 2015 and Ohio River Basin (Zhao & Beighley, 2016). In this application, the NLDAS domain was delineated into 74,075 river reaches and catchments based on a derived river network using a threshold area of roughly 100 km 2 .…”
Section: Model Set-up Calibration and Evaluationmentioning
confidence: 99%
“…The kinematic wave method is used for lateral transport of surface and subsurface runoff, while the diffusion wave (Muskingum-Cunge) method is used for river routing. The model has been applied in many regions, such as the Amazon (Beighley et al, 2009), Congo (Beighley et al, 2011), Susquehanna (Ray et al, 2016;Seyyedi et al, 2014Seyyedi et al, , 2015 and Ohio River Basin (Zhao & Beighley, 2016). In this application, the NLDAS domain was delineated into 74,075 river reaches and catchments based on a derived river network using a threshold area of roughly 100 km 2 .…”
Section: Model Set-up Calibration and Evaluationmentioning
confidence: 99%
“…Fortunately, recent advances in remote sensing have shown promise in addressing these inadequacies [9][10][11][12][13][14][15]. Satellite remote sensing datasets have been increasingly employed as an ancillary source of essential hydrologic measurements used for understanding and modeling hydrologic fluxes.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that the precision of satellite products is dependent on a number of factors such as the terrain, precipitation type, and climate [15,27,28]. A number of studies have investigated the uncertainties of satellite precipitation over varying climatic, geographic, and topographic regimes, where it is known to both under-or overestimate actual precipitation [29][30][31][32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…spatial variability, rain rate distributions, missing or falsely detecting rainfall areas), which lead to propagation in flow simulations. There are several studies (Brocca et al , ; Khan et al , ; Seyyedi et al , ) in the literature that have reported on these error differences in both precipitation and hydrological simulations. The added value of this study is that it examined those differences in the flood frequency domain rather than evaluating coincidental flow time series.…”
Section: Discussionmentioning
confidence: 99%